Womanhood and girlhood in twenty-first century middle class Kenya : disrupting patri-centered frameworks - Muhonja, Besi Brillian (Critical African studies in gender and sexuality., 2018)
This study of twenty-first century girlhoods and womanhoods charts a new area of scholarship on Kenya. The chapters investigate questions related to how new rituals of girlhood and womanhood that materialize when religious, Indigenous, and foreign worlds encounter each other are restructuring family and society, recasting roles, and informing frech conceptualization of African girlhood and womanhood. Muhonja's interdisciplinary analysis and writing journeys through the different stages of girlhood and womanhood as ritualized by Kenya's twenty-first century middle class and teases out the implications of these peculiarities to identity (re)creation and the restructuring of societies' organs, and traditionally gendered institutions--back cover.